2010
DOI: 10.1259/dmfr/50171873
|View full text |Cite
|
Sign up to set email alerts
|

The relation between bone mineral density in the heel and pixel intensity in the mandibular jaw bone among elderly women

Abstract: Objectives: The purpose of this study was to investigate the correlation between pixel intensity (PI) in digital radiographs of the lower jaw and bone mineral density (BMD) in the heels of post-menopausal women (as measured with DXL, a combination of dual energy Xray absorptiometry and lasers). Methods: Two intraoral periapical digital radiographs were taken in the right and left mandible premolar region, and the digital images were analysed by a computer program (Dimaxis) regarding PI. As the radiographs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Other investigators also found a correlation between mandibular density and skeletal BMD. [20][21][22] Another interesting finding of our study was that mandibular density showed a significant square trend in relation to age. The density decreased until the age of 54 years and became constant until age of 64 years.…”
Section: Discussionsupporting
confidence: 55%
“…Other investigators also found a correlation between mandibular density and skeletal BMD. [20][21][22] Another interesting finding of our study was that mandibular density showed a significant square trend in relation to age. The density decreased until the age of 54 years and became constant until age of 64 years.…”
Section: Discussionsupporting
confidence: 55%
“…36 Hedström et al found the pixel intensity of mandible radiograph image shows the strongest correlation to BMD in 70-74-year age group. 27 Furthermore, Jonasson et al who investigate alveolar bone mass on digital radiographs using pixel intensity distribution, reported that BMD in women correlated with bone mass by assessing the pixel intensity. 37 In present study, the black pixel values are associated with marrow space of trabecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 According to Hedström et al, pixel intensity value in digital mandible radiographs has positive correlation with BMD from the heel. 27 The pixel intensity is a measurement on a grayscale image between zero (black) to 255 (white), it is a useful method to assess bone mass. 28,29 As X-rays pass through the bone, they are influenced by the distribution of the trabeculae structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of the relevant studies remain contradictory, measuring radiographic density appears to be a promising approach for predicting osteoporosis. Indices using CBCT 35 and periapical radiographs 53 54 for this purpose had the third-highest and the fifth-highest IDIOS scores (10.25 [68.33%] and 9.02 [60.11%], respectively). This approach was not thoroughly evaluated in the literature for panoramic radiography (no study reported the SN and SP of radiographic density assessed using panoramic radiography), hence its IDIOS score was low (1 [6.7%]).…”
Section: Discussionmentioning
confidence: 99%